Suppression of VAMP2 Alters Morphology of the Tegument and Affects Glucose uptake, Development and Reproduction of Schistosoma japonicum - Qian Han (Nature Portfolio, 2017)
Abstract Schistosomiasis caused by schsitosomes is a serious global public health concern. The tegument that surrounds the worm is critical to the schistosomes survival. The tegument apical membrane undergoes a continuous process of rupture and repair owing to membranous vacuoles fusing with the plasma membrane. Vesicle-associated membrane protein 2 (VAMP2), a member of soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNAREs) is required for membrane fusion. Here, we used RNA interference (RNAi) to knock down the expression of VAMP2 of Schistosoma japonicum (SjVAMP2), and both real-time PCR and western blot analysis confirmed the suppression of this molecule, as well as the suppression of the transcript levels of schistosome glucose transporters (SGTP1 and SGTP4), and insulin receptors (SjIR1 and SjIR2). SjVAMP2-suppressed worms exhibited a lower viability, and phenotypic alterations were also observed in the tegument. Moreover, the glucose consumption of SjVAMP2-suppressed worms decreased significantly in 4 and 6 days, respectively, as well as a significant reduction in egg production. We also observed a significant reduction in worm burden and hepatic eggs burden in two independent RNAi experiment in vivo, and minor pathological changes in mice treated with SjVAMP2 specific small interfering (si)RNA. These findings reveal that SjVAMP2 may play important roles in the maintenance of tegument, glucose uptake, worm development and egg production in schistosomes.